Game-based learning in a production engineering course in Brazil - Machado, Bruna Andrade [UNESP]; De Souza, Fernando Bernardi [UNESP]; De Souza Rodrigues, José [UNESP]; Hotta, Bárbara Yumi [UNESP] (My University, 2021)
Production Management courses are key points in Production Engineering programs. Teaching concepts of Lean Manufacturing and Theory of Constraints (TOC) is an arduous task, since it involves the need to establish several important fundamentals. Traditional classes based on blackboard and speech tend to bring monotony and lack of interest to students, reducing their retention of content. On the other hand, there are active teaching methodologies that allow these concepts to be better worked and fixed. Among these methodologies is the Game-Based Learning (GBL). Based on the use of games for educational purposes, GBL allows simulate some scenarios and teach concepts, while take decisions. For about ten years, Production Management (III and IV) classes at the researched institution have been held with the support of different games: the “Beer Game” and the “Lean Board Game”, in physical format and “Goldratt Simulator”, a virtual simulator. Although the teacher of the subjects understands the importance of using games to complement the classes and understanding the concepts covered, this application had not been the target of previous researches. In 2020, a research focused on the use of games in Production Engineering courses resulted in the implementation of steps and methods in order to analyse the gains from the implementation of the games in the subjects. The research model adopted divides students into a control group and a test group, with the application of learning and perception assessments by the participants.
Keywords: Active methodologies; Game-based learning; Games; Production engineering